Alexandre Herculano: The Art and the Science of the Lusitanian Master - Ochiussi, Glener [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2018)
This work intends to analyze two of the central works of Alexandre Herculano, both essential to the formation of the Portuguese canon: O Bobo and Historia de Portugal - I. The first was extremely important to the introduction of historical novel in Portugal. The second represents a milestone for the Portuguese historiography. Given these analyzes, we conclude that in both Herculano's works, science and art are intersected.
Keywords: Alexandre Herculano; French historiography; Portuguese literature; Portuguese Romanticism